Statut pondéral et pratiques alimentaires des jeunes en Algérie [Ponderal status and food practices of youth in Algeria] - Corinne Colette DAHEL-MEKHANCHA (Nutrition & Santé, 2016)
The major socio-economic changes have affected the Algerians life resulting in increased non communicable diseases and obesity. Algerian youth who have not reached their optimum genetic potential are facing changes in their diet.Transition is observed at nutritional status and physical activity. In general, thinness and stunting are present in children, while older girls are less active and have higher body mass index and fat mass. Physical inactivity and body image dissatisfaction characterized this population. These subjects go away from traditional Algerian diet in search of new taste and gustatory pleasure that they easily found in cheap industrial products (sweet and salty with high energy density) and street food or fast-food type which altered recommended dietary balance. Moreover, school life influence resulted in the destructuration of food behavior such as a lack of breakfast, snaking and shifted schedules.It is a matter of helping this population, subject to social and family pressure, to set up trust in itself, so that nutritional recommendations are accepted without inducing new eating disorders.Nutritionists must be able to diffuse nutritional recommendations through education and healthauthorities. The contribution of media and social networks in this dissemination is fundamental and must include social, cultural and economic dimensions forimproving and diversifying traditional diet.